Science and Social Learning Tools based on Artificial Intelligence (AI) in growing Elementary Schools’ Digital Literacy - Faizal; Khoirunnisa; Budiono, Hendra (LPPM Undiksha, 2025)
Artificial Intelligence (AI) based science learning devices have yet to be used optimally because teachers are still focused on conventional learning devices that are not IT-based. This study aims to produce science learning devices to foster digital literacy in Elementary Schools. The approach to this research is a mixed method with the type of Research and Development using the ADDIE development model. The feasibility test includes the level of validity and practicality. The data collection method uses a questionnaire. The data collection instrument uses a validity and practicality questionnaire. The study results showed a level of validation with an average percentage of 92.2% in the very valid category. The level of material validity is 90% in the very valid category. Language validation with an average of 94% in the very valid category. Media validation with an average of 92.6% in the very valid category. The level of practicality obtained an average percentage value of 87% in the convenient category, teacher response of 90% (very practical), and student response of 84% (practical). The data analysis results showed that students' average pre-test score before using AI-based Learning Devices (Modules) was 62.97, and after (post-test), it was 79.41, so student learning outcomes increased. The study results indicate that artificial intelligence (AI)-based IPAS learning devices for fostering digital literacy in elementary schools are feasible to use in the learning process. The implications of the research are that the developed IPAS learning tools can be used by teachers to improve digital literacy in students.